EFEKTIVITAS MODEL MISSOURI MATHEMATICS PROJECT (MMP) DAN REALISTICS MATHEMATICS EDUCATION (RME) TERHADAP PRESTASI BELAJAR DITINJAU DARI KEMAMPUAN AWAL - Lubis, Eva Monika Safitri (DIRASATUL IBTIDAIYAH, 2023)
This study aims to determine the effectiveness of the collaboration of the Missouri Mathematics Project and Realistics Mathematics Education models with students using conventional learning models on mathematics learning achievement in terms of students' initial abilities. The population of this research was the seventh grade students of MTs Mardiyah Panyabungan. Random Sampling is used to choose the students as a sample, data analysis using descriptive test, and normality test, paired sample test, variance homogeneity test and analysis of hypothesis testing. The results of the data analysis test are 1) there are differences in learning achievement from the experimental class and the control class 2) the increase in learning achievement of the experimental class is higher than the control class. Based on these results, the effectiveness of the Missouri Mathematics Project and Realistics Mathematics Education models in improving students' mathematics learning achievement can be a recommendation for teachers or practitioners.Keywords: Missouri Mathematics Project    and Realistic Mathematics Education, Learning Achievement, and Early Ability